From the traditional to the modern and complex agricultural companies that are using business intelligence tools - Antoniu Ovidiu Balint (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
In the current conditions of a volatile economic environment, the ability to use an intelligent way the information that allows agricultural companies to cope with the challenges that they are facing regarding the current economic environment, represents the solution to strengthen their position on the global market. I explain in this paper how in the prospects of adapting intelligent business solutions they can influence not only agricultural companies but also the whole economic system. To remain competitive in the new global environment, characterized by an increasingly sharp competition, companies must adapt to new technologies and solutions.
Keywords: 330; intelligent systems; agricultural companies; economic development; business intelligence; support system